2015
DOI: 10.1111/ijac.12401
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Sr1–xBixFe0.6Sn0.4O3 Thermistor Ceramics

Abstract: Bi x Sr 1Àx Fe 0.6 Sn 0.4 O 3 (0.2 ≤ x ≤ 0.6) thermistor ceramics were prepared by conventional solid-state reaction method. The Bi substitution affected the crystalline structure and induced the decrease of lattice parameters a, b, and c in Bi x Sr 1Àx Fe 0.6 Sn 0.4 O 3 ceramics, except for x = 0.6. The values of room-temperature resistivity, thermistor constant, and activation energy of Bi x Sr 1Àx-Fe 0.6 Sn 0.4 O 3 ceramics were 7.05-6790 kΩ.cm, 4375-6694 K, and 0.378-0.578 eV, respectively. Electrical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Therefore, cation migration does not easily occur in perovskites even at high temperatures, which is why they exhibit stable electrical characteristics at high temperatures. Based upon the above results, the measured electrical performance values meet the requirements for use as industrial NTC thermistors (Yuan et al, 2015). It is therefore concluded that the partial composites of LaMnO 3 for Bi 0.2 Sr 0.5 La 0.3 TiO 3 are ideal for a wide range of practical applications as NTC thermistors.…”
Section: Figuresupporting
confidence: 59%
“…Therefore, cation migration does not easily occur in perovskites even at high temperatures, which is why they exhibit stable electrical characteristics at high temperatures. Based upon the above results, the measured electrical performance values meet the requirements for use as industrial NTC thermistors (Yuan et al, 2015). It is therefore concluded that the partial composites of LaMnO 3 for Bi 0.2 Sr 0.5 La 0.3 TiO 3 are ideal for a wide range of practical applications as NTC thermistors.…”
Section: Figuresupporting
confidence: 59%
“…The inset shows the fitting line of the copper-based thermistor logarithmic resistance–temperature curve in the temperature range from −40 to 20 °C to calculate the material constant of thermistor ( B value) by Arrhenius formula. The B value is equal to 2678 K. (d) Comparison between our copper-based thermistor with the preceding studies about thermistors in terms of temperature sensitivity ( B value) and available temperature sensing range. ,,,,, …”
Section: Resultsmentioning
confidence: 92%
“…(b) The added oxygen vacancies resulting from the Zn 2+ substitution for Ti 4+ are responsible for the increased ionic conductivity. The oxygen vacancies are created by the following defect reaction equation, ZnOZnTi··+normalOnormalO×+normalVnormalO·· . (c) The electrical conductivity in these compounds also may be due to the variable valency of titanium.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the NTC thermistors are generally characterized by two parameters: ρ , the resistivity of thermistors and B, the thermal constant which indicates sensitivity to temperature excursions. Traditionally, most NTC materials are Ni‐ and Mn‐based spinel oxides, but the application of spinel NTC thermistors is commonly limited to temperatures below approximately 200°C . Recently, high temperature NTC materials received much attention with the growing need for exhaust gas and catalytic converter temperature sensing.…”
Section: Introductionmentioning
confidence: 99%